The association between cinacalcet use and missed in‐center hemodialysis treatment rate. Issue 11 (27th June 2016) - Brunelli, Steven M.; Sibbel, Scott; Dluzniewski, Paul J.; Cooper, Kerry; Bensink, Mark E.; Bradbury, Brian D.
Abstract: Purpose: Missed in‐center hemodialysis treatments (MHT) are a general indicator of health status in hemodialysis patients. This analysis was conducted to estimate the association between cinacalcet use and MHT rate. Methods: We studied patients receiving hemodialysis and prescription benefits services from a large dialysis organization. Incident cinacalcet users were propensity score matched to controls on 31 demographic, clinical, and laboratory variables. We applied inverse probability (IP) of censoring and crossover weights to account for informative censoring. Weighted negative binomial modeling was used to estimate MHT rates and pooled logistics models were used to estimate the association between cinacalcet use and MHT. Results: Baseline demographic and clinical variables included serum calcium, phosphorus, parathyroid hormone, and vitamin D use, and were balanced between 15, 474 new cinacalcet users and 15, 474 matched controls. In an analysis based on intention‐to‐treat principles, 40.8% of cinacalcet users and 46.5% of nonusers were censored. MHT rate was 13% lower among cinacalcet initiators versus controls: IP of censoring weighted incidence rate ratio was 0.87 (95% confidence interval [CI]: 0.84–0.90 p < 0.001). In analyses based on as‐treated principles, 72.8% and 61.5% of cinacalcet users and nonusers, respectively, crossed over or were censored. MHT rate was 15% lower among cinacalcet initiators versus controls: IP of censoring/crossover weighted incidence rate ratio was 0.85 (95%CI: 0.82–0.87 p < 0.001). Conclusions: After controlling for indication and differential censoring, cinacalcet treatment was associated with lower MHT rates, which may reflect better health status. Copyright © 2016 John Wiley & Sons, Ltd.